INTERRELATION OF THE CLUB ROTATION FREQUENCY WITH THE POWER INDICATORS OF HANDS OF HIGHLY QUALIFIED FIELD HOCKEY PLAYERS - Shishkov I.Yu. ,; Furaev A.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to establish the relationship between the frequency of rotation of the club and the power indicators of the hands of hockey players on the grass of high qualification. Methods and structure of the study. 16 hockey players of the Russian national field hockey team took part in the study process. The indicators of the strength of the right and left hand (N) were studied, the force coefficient (%) and the club rotation frequency for 15 s (number of times) were calculated. Results and conclusions. The conducted correlation and regression analysis showed a statistically significant p<0.05 negative relationship between the differences in the strength of the hands and the number of rotations of the left hand in 15 s (r=-0.623). The greater the difference in the level of strength (N) of the development of the left hand in relation to the right hand, the more rotations the athletes perform with their left hand.